THE EFFECT OF PAPAYA (Carica papaya L.) SEED EXTRACT THROUGH DRINKING WATER ON THE PERFORMANCE OF BROILER CHICKEN AGED 0-4 WEEKSS - N. M. A., Dewi; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika, 2022)
This study aims to determine the effect of giving papaya seeds extract through drinking water on the performance of broiler chickens aged 0-4 weeks. This research was conducted in Selanbawak Village, Marga District, Tabanan Regency, Bali which was carried out for 4 weeks. The design used was a completely randomized design with 4 treatments and 4 replications each containing 5 broilers, so that the totally 80 number of broilers was used was 80. The treatments were broiler chickens that were given drinking water without papaya seed extract (A), broiler chickens treated with 1% papaya seed extract in drinking water (B), broiler chickens treated with 2% papaya seed extract in drinking water (C). ), broiler chickens treated with 3% papaya seed extract in drinking water (D). The variables observed were ration consumption, drinking water consumption, weight gain, final body weight, and fead convertion ratio (FCR). The results showed that the 1% (B),2%(C) and 3%(D) treatment of papaya seed extract through drinking water had no significant effect (P>0.05) on ration consumption, drinking water consumption, weight gain, final body weight, and FCR than broiers given drinking water without papaya seed extract (A). From this study it can be concluded that the treatment 1%, 2% and 3% of papaya seed extract through drinking water had no significant effect on increasing the performance of broiler chickens aged 4 weeks. Keywords: Broiler chicken, Papaya seed extract, Broiler chicken performance